2017
DOI: 10.1093/bja/aex227
|View full text |Cite
|
Sign up to set email alerts
|

Benefit and harm of pregabalin in acute pain treatment: a systematic review with meta-analyses and trial sequential analyses

Abstract: Pregabalin has demonstrated anti-hyperalgesic properties and was introduced into acute pain treatment in 2001. Our aim was to evaluate the beneficial and harmful effects of pregabalin in postoperative pain management. We included randomized clinical trials investigating perioperative pregabalin treatment in adult surgical patients. The review followed Cochrane methodology, including Grading of Recommendations Assessment, Development, and Evaluation (GRADE), and used trial sequential analyses (TSAs). The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 103 publications
4
78
0
5
Order By: Relevance
“…The included trials were assessed for risk of bias according to the Cochrane Handbook and we decided a priori to report and conclude based on primarily results from trials classified as low risk of bias . The following domains were assessed: random sequence generation, allocation concealment, blinding, incomplete outcome data, selective outcome reporting, and other bias, including funding and confirmation bias .…”
Section: Methodsmentioning
confidence: 99%
“…The included trials were assessed for risk of bias according to the Cochrane Handbook and we decided a priori to report and conclude based on primarily results from trials classified as low risk of bias . The following domains were assessed: random sequence generation, allocation concealment, blinding, incomplete outcome data, selective outcome reporting, and other bias, including funding and confirmation bias .…”
Section: Methodsmentioning
confidence: 99%
“…Several old reviews and meta-analyses have highlighted a pain-relieving effect of preoperative administration of gabapentin on pain in the first postoperative days [18][19][20][21][22]. In contrast, more recent reviews have highlighted that gabapentinoids might have minimal opioid sparring effect in the acute postoperative phase, but the severe adverse events are increased [24], and the evidence is based on low quality studies [23]. A recent review on the effect of preoperative administration of gabapentin and pregabalin prior to breast cancer surgery found no associations between the administration of either drug on the development of chronic postoperative pain [39].…”
Section: Effects Of Gabapentinoids On Chronic Postoperative Painmentioning
confidence: 99%
“…Several older reviews and meta-analyses [18][19][20][21][22], concludes that gabapentinoids reduce pain in the first postoperative days. However, recent meta-analyses have shed critical light on most of the perioperative gabapentinoid literature and concluded that the quality of evidence is low, firm evidence for the use in postoperative pain management is lacking, the clinically relevant beneficial effect seems absent, and there may be a risk of harm [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, las evaluaciones GRADE mostraron evidencia de calidad moderada a muy baja. En consecuencia, según los autores, no se puede recomendar el uso habitual de pregabalina para el tratamiento del dolor postoperatorio debido a su baja eficacia como ahorrador de opioides (25).…”
Section: Gabapentinoides (Gabapentina Y Pregabalina)unclassified